2016
DOI: 10.1590/1516-3180.2015.0241030516
|View full text |Cite
|
Sign up to set email alerts
|

Medication and nutritional supplement use before and after bariatric surgery

Abstract: CONTEXT AND OBJECTIVE: Bariatric surgery has been an effective alternative treatment for morbid obesity and has resulted in decreased mortality, better control over comorbidities and reduced use of drugs. The objective of this study was to analyze the impact of bariatric surgery on medication drug and nutritional supplement use. DESIGN AND SETTING: Longitudinal study of before-and-after type, on 69 morbidly obese patients in a public hospital in Porto Alegre. METHODS: Through interviews, the presence of comorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 75 publications
(76 reference statements)
1
5
0
10
Order By: Relevance
“…The results are comparable to Backes et al study in 2016 which revealed that the most common comorbidities during the postoperative phase were hypertension (29.7%), followed by diabetes (6.3%) and dyslipidemia (6.3%) [19]. Unlikely, the percentage of those with hypertension were lower in our study as compared to Backes et al study but diabetes percentage was higher in the Lebanese bariatric population [19].…”
Section: Patients Characteristicssupporting
confidence: 82%
See 2 more Smart Citations
“…The results are comparable to Backes et al study in 2016 which revealed that the most common comorbidities during the postoperative phase were hypertension (29.7%), followed by diabetes (6.3%) and dyslipidemia (6.3%) [19]. Unlikely, the percentage of those with hypertension were lower in our study as compared to Backes et al study but diabetes percentage was higher in the Lebanese bariatric population [19].…”
Section: Patients Characteristicssupporting
confidence: 82%
“…Sleeve gastrectomy was the most performed (57.7%) bariatric surgery in our study, followed by roux-eny gastric bypass (27%) and gastric banding (15.3%). Unlikely, in Backes et al study, the surgical technique most often used was gastric bypass (91.4%) [19].…”
Section: Type Of Surgerymentioning
confidence: 85%
See 1 more Smart Citation
“…There is consistent evidence that surgical treatment of obesity results in more favorable weight loss and weight-associated comorbidity outcomes compared with nonsurgical interventions (1,2), with a positive impact on preexisting diabetes and hypertension, among others (3,4). A lower risk of developing type 2 diabetes (T2D), hypertension, angina, myocardial infarction, and obstructive sleep apnea after bariatric surgery has also been reported (4).…”
Section: ' Introductionmentioning
confidence: 91%
“…A lower risk of developing type 2 diabetes (T2D), hypertension, angina, myocardial infarction, and obstructive sleep apnea after bariatric surgery has also been reported (4). The improvement or resolution of comorbidities is likely to entail reduced medication use and expenditure following bariatric surgery (3).…”
Section: ' Introductionmentioning
confidence: 99%